Teacher’s Resilience Strategies during Covid-19 Pandemic: Reflections From Students’ Perspectives (Conference on English Language Teaching, 2023)
This research explores the resilience strategies employed by EFL teachers during the Covid-19 pandemic and their subsequent impact on students' engagement and motivation. The study employs a mixed-method approach, combining a questionnaire distributed among 84 students and interviews conducted with 8 students. Analysis of the data is carried out using Miles and Huberman's qualitative analysis method. The research reveals that EFL teachers who effectively integrated technology tools such as Zoom and Google Meet demonstrated a higher level of resilience. Students' perceptions indicated that these strategies not only sustained their concentration during online sessions but also fostered enthusiasm and motivation for learning. The findings corroborate previous research emphasizing the role of adaptive teaching approaches and technology integration in enhancing student engagement. The study concludes by suggesting further exploration into the long-term impacts of these strategies on academic performance and the challenges in implementing technology-driven teaching methods. This research contributes to the understanding of EFL teachers' resilience and its correlation with students' learning experiences amid the challenges posed by the Covid-19 pandemic.